Functionalized lipid-based drug delivery nanosystems for the treatment of human infectious diseases - Almeida Furquim de Camargo, Bruna [UNESP]; Fonseca-Santos, Bruno; Gonçalves Carvalho, Suzana [UNESP]; Corrêa Carvalho, Gabriela [UNESP]; Delello Di Filippo, Leonardo [UNESP]; Sousa Araújo, Victor Hugo [UNESP]; Lobato Duarte, Jonatas [UNESP]; Polli Silvestre, Amanda Letícia [UNESP]; Bauab, Taís Maria [UNESP]; Chorilli, Marlus [UNESP] (Taylor & Francis, 2022)
Infectious diseases are still public health problems. Microorganisms such as fungi, bacteria, viruses, and parasites are the main causing agents related to these diseases. In this context, the search for new effective strategies in prevention and/or treatment is considered essential, since current drugs often have side effects or end up, causing microbial resistance, making it a serious health problem. As an alternative to these limitations, nanotechnology has been widely used. The use of lipid-based drug delivery nanosystems (DDNs) has some advantages, such as biocompatibility, low toxicity, controlled release, the ability to carry both hydrophilic and lipophilic drugs, in addition to be easel scalable. Besides, as an improvement, studies involving the conjugation of signalling molecules on the surfaces of these nanocarriers can allow the target of certain tissues or cells. Thus, this review summarizes the performance of functionalized lipid-based DDNs for the treatment of infectious diseases caused by viruses, including SARS-CoV-2, bacteria, fungi, and parasites.
Keywords: drug delivery nanosystem; functionalization; infectious diseases; nanotechnology; Targeting